Pengaruh Literasi Keuangan, Gaya Hidup, Pengendalian Diri dan Media Sosial Terhadap Perilaku Konsumtif Pembelian Iphone (Survei pada Mahasiswa Universitas Slamet Riyadi Surakarta) - Oktaviana, Rizka Azimatul; Wibowo, Edi (Teewan Journal Solutions, 2025)
Financial management refers to a series of activities that focus on managing financial resources effectively and efficiently. This study aims to examine the influence of financial literacy, lifestyle, self-control, and social media exposure on individual consumptive behaviour, especially in the context of purchasing premium products such as iPhones. This research is a survey of Slamet Riyadi University Surakarta students who use iphone. The type of data used is quantitative data. The data source used is primary data. The population in this study were iphone user students at Slamet Riyadi University Surakarta. The number of samples used in this study were 100 people. This data collection technique uses a questionnaire. This data analysis uses multiple linear regression tests, t tests, F tests, and determination coefficient tests. The results of the t test show that financial literacy (X1) price has no significant effect on consumptive behaviour, lifestyle (X2) has a significant effect on consumptive behaviour, self-control (X3) has no significant effect on consumptive behaviour, and social media (X4) has no significant effect on consumptive behaviour